The University of Iowa guide to campus architecture - Scott, John Beldon, 1946- (Bur Oak guide., 2006)
The University of Iowa boasts an outstanding ensemble of buildings whose stylistic diversity reflects the breadth of Iowa's contributions to research, education, and creative activities. In this first comprehensive guide to the university's architecture, authors John Scott and Rodney Lehnertz reveal the artistic integrity, intellectual inspiration, and cutting-edge function of the campus buildings. Scott and Lehnertz highlight seventy-eight buildings that they consider architecturally significant, from the Greek Revival style of Old Capitol at the center of the Pentacrest, designed by John Fra.